Efeitos da suplementação de chia (salvia hispanica L.) Sobre a pressão arterial, estresse oxidativo, inflamação e modulação autonômica cardíaca em indivíduos hipertensos: um estudo de intervenção - Toscano, Luciana Tavares (2014)
Hypertension is a multifactorial condition treated by pharmacological and complementary measures such as nutritional approach. In this context, Chia (Salvia hispanica L.) stands out for its nutritional, antioxidant and anti-inflammatory composition. However, it has not yet been elucidated if Chia can reduce blood pressure in hypertensive individuals, and which factors are responsible for this effect. In this context, the present study aimed to verify the effect of supplementation of chia (Salvia hispanica L.) on blood pressure and assess if oxidative stress, inflammation, endothelial function and cardiac autonomic modulation are factors associated with lowering blood pressure in hypertensive individuals treated or not. Thus, a double-blind, randomized controlled trial was conducted with 26 hypertensive individuals. Among these, seventeen treated individuals were randomized to consume chia (CHIA-MD n = 10) and placebo (PLA-MD n = 7). Another group of untreated hypertensive individuals was formed (CHIA-NM, n = 9). They consumed 35 g/day or placebo chia flour 12 weeks. Clinical and ambulatory blood pressure, cardiac autonomic modulation, oxidative stress, inflammation and a marker of nitric oxide production were measured at baseline and after intervention. While PLA-MD group showed no significant change in mean of clinic blood pressure (from 108.0±2.9 to 105.7±2.9 mmHg, p=0.70), it was observed this reduction in GHIA group (from 111.5±1.9 to 102.7±1.5 mmHg, p < 0.001) and CHIA-MD (from 111.3±2.2 to 100.1±1.8 mmHg, p < 0.001), it there was no significant reduction in CHIA-NM (111.7±2.9 para 105.7±2.9 mmHg, p=0.05). In CHIA group, blood pressure reduction was was due to the reduction in both systolic (146.2 ± 2.0 to 136.3 ± 2.6 mmHg, p <0.01) and diastolic components (94.2 ± 2.0 to 85.5 ± 1.2, p <0.001). The same results occurred in CHIA-MD (145.8 ± 2.2 to 133.7 ± 4.1 mmHg, p <0.01 and 94.3 ± 2.4 to 83.3 ± 1.3 mmHg, p <0.01) for systolic and diastolic components, respectively. CHIA-NM group had only reduced systolic blood pressure (146.8 ± 3.8 to 137.3 ± 3.1 mmHg, p <0.05). These reductions in clinical blood pressure were confirmed by ambulatory systolic blood pressure in all supplemented groups in periods of 24 hours, wakefulness and sleep. On the other hand, the ambulatory diastolic pressure did not change in either group. The hypotensive effects of chia were accompanied by reduction in lipid peroxidation in CHIA groups (p = 0.04) and Chia-NM (p = 0.02) compared to PLA-MD. The hypotensive effects of chia were accompanied by reduction in lipid peroxidation in CHIA (p = 0.04) and CHIA-NM (p = 0.02) compared to PLA-MD. CHIA group also showed a reduction of plasma nitrite (p = 0.02). Inflammation and cardiac autonomic modulation remained unchanged. It was concluded that consumption of chia flour is able to reduce blood pressure in hypertensive individuals treated or not, both clinically and ambulatory. This phenomenon was accompanied by reduced lipid peroxidation, but no alterations in inflammatory markers and cardiac autonomic modulation were seen.